Farewell to Democracy? An analysis of Uribe Velez’s Peace Policies Incidence on the Democratic Institutions of Colombia - Gamboa Tapias, Camila de (Estudios de Filosofía, 2010)
The aim of this article is to offer an analysis of the Peace Policies of Uribe Vélez’s Government and their effects on Colombian Democratic Institutions and Political Culture. I will not evaluate directly if the said Peace Policies were successful in ending the Internal Political Conflict of Colombia, but rather to show that the link between a weak Institutional Democracy, such as Colombia`s, the great influence of Uribe Vèlez`s personality in the Political Imaginary and his projects of Democratic Security and of a Communitarian State, in so far as these projects were part of his Peace Policies. The central thesis I defend in this article is that precisely Colombia`s democratic weakness enabled that a Policy such as Álvaro Uribe`s in relation to peace was supported by a large part of the population, even though this Policy instead of strengthening Democracy weakened more its Institutions and Political Culture.